Environmental Sustainability Initiatives in the Operating Room: A Scoping Review - Emre Gorgun, MD; Sumudu Dehipawala, MPH; Matthew O’Hara, MBA; Elena Naoumtchik, MSc; Gaurav Gangoli, PharmD; Crystal Ricketts, PhD; Giovanni A. Tommaselli, MD, PhD (Annals of Surgery Open, 2024)
The global healthcare industry has a substantial environmental footprint and therefore has a responsibility to decrease its impact. Changes to increase sustainability will only occur if healthcare providers (HCPs) and decision-makers understand and incorporate environmentally conscious practices in the operating room (OR). This scoping review aimed to assess hospital initiatives undertaken to support environmental sustainability in the OR, with a focus on HCP and hospital decision-maker beliefs and perceptions related to sustainability. A scoping review was conducted using Embase and PubMed. Searches were performed to identify relevant studies published between January 2011 and November 2022. A total of 163 publications were included: 10 systematic literature reviews and 153 original research articles. Most studies reported department-wide sustainability measures (waste reduction, staff education, etc), which were evaluated by the reduction in generated waste and energy, emission of greenhouse gasses, and costs. Despite up to 97% of HCPs noting willingness to improve sustainability within practices, up to 80.9% of HCPs stated that they lacked the necessary training and information. In conclusion, this research highlights a recent increase in interest about sustainability initiatives in the OR and that HCPs and surgical staff are not only willing to participate but also have suggestions on how to minimize the environmental impact of the OR.